Radicalism and Liberalism according to Emma Goldman - Janečková, Erika (Univerzita Pardubice, 2017)
This bachelor thesis deals with the analysis and comparison of radical and liberal views in selected essays of Emma Goldman - primarily in "What I Believe," "Anarchism: What It Really Stands for," "Was My Life Worth Living?" and "The Individual, Society and the State." The theoretical part provides the historical and cultural overview of the late 19th - early 20th century United States, and the theoretical background necessary for the analysis. In the practical part, Goldman's conception of individual freedom together with her views on the government, property, religion and violence are analyzed. The analysis also focuses on changes in Goldman's views throughout the years.
Porovnání radikalismu a liberalismu ve vybraných pracích Emmy Goldman
Keywords: radicalism; anarchism; liberalism; Emma Goldman; individualism; freedom; radikalismus; anarchismus; liberalismus; Emma Goldman; individualismus; svoboda